Economía circular: una contribución a la competitividad dentro de la industria textil colombiana. (2021)
The environmental impact has generated the creation of new options for sustainable production, one of them is the circular economy model where under 3 principles mainly, a company changes some if it is not all phases of its production process. One of the industries that produces the most pollution is the textile industry, so the following work seeks to establish how the circular economy can contribute to competitiveness within the Colombian textile industry, taking into account the Canvas model to compare two companies: Textiles Lafayette S.A.S that follows the fundamentals and principles of the circular economy and , on the contrary Coltejer S.A that continues a production process under the linear economy.